Developing Foreign Language Teacher Standards in Uruguay - Kuhlman, Natalie A. (GIST – Education and Learning Research Journal, 2010)
This article documents the development of foreign language (FL) teacher standards in Uruguay. It begins by discussing what it means to be a teacher, what standards are and are not, and how they can be helpful or misused in teacher development. In the proposal, a distinction is made between teacher preparation programs that are course-based and those that are standards-based, where standards cross particular course boundaries. Finally, the collaborative process used to develop the standards for the situation in Uruguay is described, which was based, fundamentally, on the TESOL p-12 ESL Teacher Preparation Standards.